Recognition of Proteins by Metal Chelation-Based Fluorescent Probes in Cells - Jiang, Nan; Li, Hongyan; Sun, Hongzhe (Frontiers in Chemistry, 2019)
Fluorescent probes such as thiol-reactive and Ni2+-nitrilotriacetate (NTA) based probes provide a powerful toolbox for real-time visualization of a protein and a proteome in living cells. Herein, we firstly went through basic principles and applications of thiol-reactive based probes in protein imaging and recognition. We then summarize a family of metal-NTA based fluorescence probes in visualization of His6-tagged protein and identification of metalloproteins at proteome-wide scale. The pros and cons of the probes as well as ways to optimize them are discussed.